1999
DOI: 10.1046/j.1432-1327.1999.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talk mechanisms in the development of insulin resistance of skeletal muscle cells

Abstract: Insulin resistance in skeletal muscle is one of the earliest symptoms associated with non-insulin-dependent diabetes mellitus (NIDDM). Tumour necrosis factor (TNF) and nonesterified fatty acids have been proposed to be crucial factors in the development of the insulin-resistant state. We here show that, although TNF downregulated insulin-induced insulin receptor (IR) and IR substrate (IRS)-1 phosphorylation as well as phosphoinositide 3-kinase (PI3-kinase) activity in pmi28 myotubes, this was, unlike in adipoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 55 publications
(67 reference statements)
6
54
1
1
Order By: Relevance
“…Our results in primary neonatal myotubes are in agreement with those obtained in muscle in vivo (18) and indicated that insulin resistance by TNF-␣ seems to be the consequence of an antagonism in the activation of the complete insulin signaling cascade from IR to Akt rather than changes on muscle gene expression. Furthermore, the significant increase in basal glucose uptake produced by TNF-␣ treatment in primary skeletal muscle cells was not due to GLUT4 translocation to the plasma membrane and seemed to be associated with increased GLUT1 expression, as has been described previously in several muscle cells (29,39).…”
Section: Inhibition Of Ikks By Salicylate or Pd* Precludes Insulin Resupporting
confidence: 76%
See 1 more Smart Citation
“…Our results in primary neonatal myotubes are in agreement with those obtained in muscle in vivo (18) and indicated that insulin resistance by TNF-␣ seems to be the consequence of an antagonism in the activation of the complete insulin signaling cascade from IR to Akt rather than changes on muscle gene expression. Furthermore, the significant increase in basal glucose uptake produced by TNF-␣ treatment in primary skeletal muscle cells was not due to GLUT4 translocation to the plasma membrane and seemed to be associated with increased GLUT1 expression, as has been described previously in several muscle cells (29,39).…”
Section: Inhibition Of Ikks By Salicylate or Pd* Precludes Insulin Resupporting
confidence: 76%
“…Ceramide and fatty acids have been reported to induce insulin resistance in skeletal muscle (27)(28)(29), and production of insulin resistance could be a consequence of sphingomyelinase or lipolytic activation by TNF-␣ (30, 31). However, a direct effect of TNF-␣ on insulin resistance in muscle, which is responsible for 80% of the glucose disposal of the body, is controversial.…”
mentioning
confidence: 99%
“…The glucose oversupply also affected the composition of phospholipids, which play an important functional role in membranes. Changes in the FA composition of phospholipids might alter membrane fluidity and permeability as was shown by the "leaky membrane" hypothesis [34], and probably diminishes insulin sensitivity due to altered insulin receptor number, reduced insulin binding capacity and/or altered insulin receptor tyrosine kinase activity [35,36,37,38] or even more due to altered post receptor signalling [39,40,41,42]. Using the same samples as in this study we found, that in rat skeletal muscle early steps of insulin signalling (phosphorylation of the insulin receptor, IRS-1 and protein kinase B and the IRS-1-associated phosphatidyl-inositol-3′-kinase activity) are inhibited after 2 and particularly after 5 days of glucose infusion [30].…”
Section: Discussionmentioning
confidence: 99%
“…13 Kym-1 cells are TNF-responsive as evident from rapid, but transient NFkB activation (Figure 2A), and the later induction of apoptosis without conditioning of the cells by protein synthesis inhibitors 29,30 ( Figure 4A). In accordance with previous results obtained in other cell models 4,5,11,12 a 2 h TNF pretreatment of Kym-1 cells resulted in a typical amelioration of the subsequent insulin response, with a partial (30 ± 50%) reduction of IRb kinase activity ( Figure 2B).…”
Section: Kym-1 Rhabdomyosarcoma Growth Depends On Functional Insulin/mentioning
confidence: 99%
“…10 ± 12 However, the partial inhibition of IRb kinase activity appears by itself not sufficient to explain reduced glucose uptake, as in muscle cells the latter is not affected by TNF despite a down-regulation of IRb kinase and immediate downstream substrates. 13 In addition to the prominent IR signal tranducer IRS-1, STAT5b was recently recognized as a direct substrate. 12,14,15 Both, IRS-1 and STAT5b are considered as important regulators of proliferative and antiapoptotic responses.…”
Section: Introductionmentioning
confidence: 99%